The impact of cognitive functioning on mortality and the development of functional disability in older adults with diabetes: the second longitudinal study on aging - Ajani Umed A; Ford Earl S; McGuire Lisa C (BMC Geriatrics, 2006)
Abstract Background For older adults without diabetes, cognitive functioning has been implicated as a predictor of death and functional disability for older adults and those with mild to severe cognitive impairment. However, little is known about the relationship between cognition functioning on mortality and the development of functional disability in late life for persons with diabetes. We examined the relative contribution of cognitive functioning to mortality and functional disability over a 2-year period in a sample of nationally representative older US adults with diabetes who were free from cognitive impairment through secondary data analyses of the Second Longitudinal Study of Aging (LSOA II). Methods Participants included 559 US adults (232 males and 327 females) ≥ 70 years old who had diabetes and who were free from cognitive impairment were examined using an adapted Telephone Interview of Cognitive Status (TICS), Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL). Results Multivariate logistic regression was conducted to investigate the independent contribution of cognitive functioning to three mutually exclusive outcomes of death and two measures of functional disability status. The covariates included in the model were participants' sex, age, race, marital status, educational level, duration of diabetes, cardiovascular disease (CVD) status, and self-rated health. Persons with diabetes who had the lowest levels of cognitive functioning relative to the highest level of cognitive functioning had a greater odds of dying (AOR = 0.80, 95% CI = 0.67–0.96) or becoming disabled (AOR = 0.87, 95% CI = 0.78–0.97) compared to those people who were disability free. Conclusion Older adults with diabetes and low normal levels of cognition, yet within normal ranges, were approximately 20% more likely to die and 13% more likely to become disabled than those with higher levels of cognitive functioning over a 2-year period. Brief screening measures of cognitive functioning could be used to identify older adults with diabetes who are at increased risk for mortality and functional disability, as well as those who may benefit from interventions to prevent or minimize further disablement and declines in cognitive functioning.